CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN APLIKASINYA DALAM INDUSTRI MANUFAKTUR DAN JASA - Edwin Agung Wibowo (Universitas Riau Kepulauan, 2014)
Customer Relationship Management (CRM) is one of the ways to maintain continuous relationship between a company and its stakeholders as well as its shareholder. A lot of companies are using CRM to maintain its relationship with the customers. By using CRM, the companies will be able to find out their customers’ needs and wants so that emotionally they can be involved with each other. This enables them to have a two-way communication. As a result, they will have close and open business relationship which makes the customers, especially, loyal to the companies; and they will not easily change their preference to another product or brand.